Lasting Impressions: Ethnic Food Tour Guides and Body Work in Southwestern Sydney. Issue 1 (26th April 2017) - Swan, Elaine; Flowers, Rick
Abstract : In this paper we examine the racialized and gendered body work required of guides leading ethnic food tours in southwestern Sydney, Australia. We draw on theorists who examine the materialization of race and bodies to extend concepts of intimacy, vulnerability and proximity: dominant themes in studies of occupations involving 'body work'. To date, very few studies of tour guides have examined the embodied interactions required by the work of guides. Using Ahmed's concepts of inter–embodiment and impressions, we stress that racialized bodies need to be understood as materializing in body work. In particular, we show how body work on the tours includes smiling, vocalization and shepherding and can be understood as contact with the Other. Our paper contributes to the literature on bodily interactions at work in three core ways: first, adding original empirical work on ethnic tour guiding, second, by showing how 'body work' is racialized and gendered, and finally, by exploring the relations between food and multicultural intimacies and the vulnerabilities of racialized bodies.